Geochemical and Sr-Nd isotopic characteristics of Upper Cretaceous (calc-alkaline) and Miocene (alkaline) volcanic rocks: Elazig, Eastern Taurides, Turkey - Kurum, Sevcan; Tanyildizi, Ozge (Pergamon-Elsevier Science Ltd, 2017)
The massive volcanic suite of Upper Cretaceous Elazig Magmatic Complex, and Miocene basic volcanic rocks of crop out to the southern vicinity of Elazig. The petrographical studies indicated that the massive volcanic suite of Upper Cretaceous are of basalt, spilitic basalt, basaltic andesite, andesite, trachite, dacite/ryolithe and dolerite in composition, and the Miocene volcanic rocks are basalt in composition. According to the geochemical data, which are conformable with the petrographical ones, Upper Cretaceous volcanic rocks are of low and medium-K contaning types and calc-alkalin in general, and enriched with respect to LILE and HREE contents. They also contain low Ti, have negative Nb and Ta anomaly and low Nd-143/(147) and high Sr-87/Sr-86 ratios. Geochemical and isotopic data for the massive volcanic suite point out that these volcanic rocks were originated from an upper mantle source (lithospheric) which. undergone fractional crystallisation and crustal contamination and enriched by these processes and metasomatized within a subduction zone. Miocene volcanic rocks are of high-K alkaline type, alkali basalt/basanite in composition and products of intraplate volcanism. These rocks are richer in some major oxide contents such as Na2O, K2O, MgO and trace element contents such as Nb, Sr, Zr compared to the massive volcanic rocks of Upper Cretaceous, and they are also enriched with respect to their LILE and HREE contents. The remarkable decrease from LREE towards HREE in the REE/Chondrite-normalized variation diagram indicates a magmatic differentiation process. The MgO and Ni ratios of Miocene volcanic rocks are not conformable with those of primitive basalt composition. However, all the chemical and isotopic (low 87Sr/86Sr ratio and positive (+) eNd values) data indicate that the source magma of these volcanic rocks was derived from a depleted garnet free magma (astenospheric mantle) and was modified once again by the post collosional geodynamical events and show interplate Zr and Th enrichment. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Cretaceous-miocene volcanic rocks; Sr-Nd isotopes; Elazig-Turkey